EFEKTIVITAS KOMITE SEKOLAH DALAM MENINGKATKAN KINERJA SEKOLAH DASAR NEGERI PERUMNAS PEUNYARENG KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Agustina Agustina; Siraj Siraj; Zahriyanti Zahriyanti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The aim of this study was to describe the effectiveness of school committees in improving the performance of Perumnas Peunyareng State Elementary School, Meureubo District, West Aceh District. Researchers used qualitative research to describe the effectiveness of school committees. Research informants are school committee chairs, school principals, committee members and teachers, and school supervisors. Data was collected through interview techniques, document study, and observation. Data analysis techniques include processes: data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data is done by testing the credibility of the data. The results of the study found that the effectiveness of the school committee in improving the performance of Perumnas Peunyareng Elementary School, Meureubo District, West Aceh Regency. The effectiveness of effective school committees includes coordinating, providing advice and corrections, accommodating and conveying aspirations, conducting supervision, checking school development from allocated funds, providing financial support, providing energy and thought support, conducting negotiations, and conveying information to the community. The effectiveness of the school committee has not been maximized in contributing to quality improvement in the field of school facilities and infrastructure, strengthening the leadership of the school principal (school management), and school finances. However, the achievement of school facilities and infrastructure has not been sufficient enough to meet school needs. There are many other components that influence besides the school committee, so that the acquisition of B accreditation can be caused by other factors not examined in this study.